2015
DOI: 10.1093/annonc/mdu504
|View full text |Cite
|
Sign up to set email alerts
|

Small-cell lung cancer detection in never-smokers: clinical characteristics and multigene mutation profiling using targeted next-generation sequencing

Abstract: Never-smokers with SCLC are increasingly prevalent and have a better prognosis than smokers with SCLC in Korea. Our study warrants further investigation in this group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
71
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(82 citation statements)
references
References 19 publications
7
71
4
Order By: Relevance
“…D. 162 patients with PNI < 45 had worse prognosis than 757 patients with PNI ≥ 45 (8.7 vs. 11.0 months, P < 0.001). status before diagnosis in the prognosis of SCLC was also evaluated and the results confirmed that non-smokers with SCLC had better prognosis than smokers, and this was consistent with results from Korea (Sun et al 2015). Smoking status was especially useful as a predictor of long-term survival in this study.…”
Section: Discussionsupporting
confidence: 88%
“…D. 162 patients with PNI < 45 had worse prognosis than 757 patients with PNI ≥ 45 (8.7 vs. 11.0 months, P < 0.001). status before diagnosis in the prognosis of SCLC was also evaluated and the results confirmed that non-smokers with SCLC had better prognosis than smokers, and this was consistent with results from Korea (Sun et al 2015). Smoking status was especially useful as a predictor of long-term survival in this study.…”
Section: Discussionsupporting
confidence: 88%
“…Compared with our study, a smaller number of SCLCs were included in their study and the histological heterogeneity might have affected their results. In addition, they used a semi-quantitative histological score, which was obtained by multiplying the percentage of reactive cells by the corresponding immunostaining intensity, as a continuous variable to evaluate immunohistochemical findings, whereas we used a binary variable, In our study, the proportion of never smokers was 24 %, which is much higher than that reported in non-Asian countries and contradicts the well-established strict relation between SCLC and cigarette smoking [14,15]. The prevalence of nonsmoking-related lung cancer, regardless of histological type, is known to be higher among Asian patients including Koreans than in non-Asian patients, and this could be explained by ethnic differences [15][16][17].…”
Section: Discussioncontrasting
confidence: 72%
“…In addition, 22 (79 %) of 28 never smokers included in this study were female. It has been reported that lung cancer develops more frequently in never-smoked women than never-smoked men [15,18]. This phenomenon suggests that there might be biological differences due to gender in the carcinogenesis of lung cancer.…”
Section: Discussionmentioning
confidence: 98%
“…The clinical characteristics and multigene mutation profiling of SCLC in never-smokers 35, 36 has been evaluated. The never-smokers with SCLC (50/391) had a better prognosis than smokers with SCLC in the Korean cohort.…”
Section: Genome Epigenome and Proteome Studiesmentioning
confidence: 99%